Ethanol sclerotherapy of head and neck venous malformations - José Luiz Orlando (Einstein (São Paulo))
Objective This retrospective study evaluated the results of sclerotherapy with low doses of ethanol for treatment of head and neck venous malformations.Methods We treated 51 patients, 37 females. Median age was 23 years. Patients were treated with percutaneous intralesional injection of alcohol every two weeks and followed up prospectively for a median period of 18 months. Most lesions affected the face and cosmetic disfigurement was the most frequent complaint.Results We performed a median of 7 sessions of sclerotherapy. Complete resolution or improvement was observed in 48 patients presented. Five cases of small skin ulceration, two cases of hyperpigmentation and two of paresthesia were documented; all of them were treated conservatively.Conclusion Percutaneous sclerotherapy with low doses of ethanol is a safe and effective treatment modality for venous malformations affecting the head and neck.